ANALISIS KESADARAN HUKUM REMAJA PELAKU PERNIKAHAN DINI DI DESA TANTAN KECAMATAN SEKERNAN KABUPATEN MUARO JAMBI - Rahayu; Hendra; Yuslistia Opeska (STKIP Subang, 2026)
Early marriage remains a critical social and legal issue in Indonesia, as observed in Tantan Village, Sekernan District, Muaro Jambi Regency. This phenomenon persists despite existing legal regulations, specifically Law Number 16 of 2019, which sets the minimum age of marriage for both men and women at 19 years. This study aims to analyze the legal awareness of adolescents who practice early marriage in Tantan Village and to identify the factors influencing their level of legal awareness. This research is expected to provide an overview of adolescents' understanding, attitudes, and legal behavior toward the applicable marriage age regulations. The methodology employed in this study is a qualitative research method with a descriptive approach. Data collection was conducted through technical triangulation. The research informants consist of adolescents practicing early marriage, parents, and representatives from the Office of Religious Affairs (KUA). Data analysis follows the stages of data reduction, data presentation, and conclusion drawing to obtain an in-depth understanding of the adolescents' legal awareness level. The results indicate that the legal awareness of adolescents practicing early marriage in Tantan Village is still relatively low. This is evident from the adolescents' limited knowledge regarding the minimum marriage age provisions, a low understanding of the purpose behind the regulation, and weak legal compliance in actual marriage practices.